2021
DOI: 10.33369/pgsd.14.1.28-37
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Student Learning Achievement Class Iv at SDN 097376 Sippan

Abstract: This study aims to determine the learning methods of the fourth grade students of SDN 097376 SIPPAN. The form of this researchis descriptive qualitative research. The subjects in this study were grade IV SDN 097376 SIPPAN. Data collection techniques in this study are observation techniques, interview techniques and documentation techniques. Based on the results of the study, it can be concluded that the way of achieving student learning is discipline of learning every night at home, repeating lessons at home f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Then, based on previous research conducted by Sinurat, Tanjung, Anzelina, & Abi (2021) found that student learning achievement is a form of habit carried out every day by students at home by learning lessons the night before entering school, reading, summarizing subject matter, practicing, and answering practice questions. With this study habit, students are able to get satisfactory and maximum learning achievements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, based on previous research conducted by Sinurat, Tanjung, Anzelina, & Abi (2021) found that student learning achievement is a form of habit carried out every day by students at home by learning lessons the night before entering school, reading, summarizing subject matter, practicing, and answering practice questions. With this study habit, students are able to get satisfactory and maximum learning achievements.…”
Section: Discussionmentioning
confidence: 99%
“…In the learning process, the teacher must also be able to make students actively involved during the learning process, then the teacher also needs to pay attention to the way students learns. Whether the way of learning http://eduvest.greenvest.co.id owned by students is appropriate and effective, by having an effective way of learning, students have a better chance of obtaining achievements or learning achievements (Sinurat et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…So that the problems faced can be minimized if you really use media and strategies according to the needs of each student. (Sinurat et al, 2021). Because in fact they have diverse characteristics in classroom learning.…”
Section: Introductionmentioning
confidence: 99%
“…perubahan yang ada pada siswa dapat menuju kearah yang baik sehingga tujuan pembelajaran yang di inginkan dapat di capai (Sinurat et al, 2021).…”
unclassified